Classroom Climate: Empirical Validation and Educational Implications of a Conceptual Model. A Multilevel Study - Jesús Alonso-Tapia; Miguel Ruiz-Díaz (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
Classroom Climate (CC) is supposed to affect students’ motivation, emotions, behavior, and learning, but the existing models are not specific enough to provide a guide for analyzing and improving it. This paper aims to provide and validate a specific CC model including four components – academic-motivational, discipline, and emotional climate created by teachers’ action patterns, and co-living climate referred to as social relationships between students; 5,471 Secondary and High School students from 262 classrooms of 27 Spain and Costa Rica schools participated in the study. Structural equation modeling showed a high structural validity of the CC model. However, the co-living climate was not an indicator of CC as good as the other hypothesized components. A multilevel analysis showed that the model is similar at both levels, student and classroom. Furthermore, path analyses showed that the effects of the CC score attributed to the teacher are higher than if CC components are used as independent though combined predictors.